Gaya Kepemimpinan dan Kompensasi dalam Memengaruhi Kinerja Karyawan pada PT. Anwar Contruction - Ahmad Ulil Albab Al Umar; Yeyen Novita; Deby Asyah Septiyanti; Pandu Nur Wicaksono; Faiz Nasokha; Muammar Taufiqi Lutfi Mustofa (Universitas Batanghari Jambi, 2022)
This study analyzes employee performance influenced by leadership style and compensation factors at PT. Anwar Construction. The method of data collection is through the distribution of questionnaires. The population of this study were all employees at PT. Anwar Construction. The sample of this study amounted to 48 respondents. The data analysis technique used multiple linear regression using the SPSS application. Testing hypotheses 1 and 2 using t test, f test and coefficient of determination test. The results of this study indicate that leadership style and compensation have a significant effect on employee performance in the company. Then, leadership style has a positive and significant influence on employee performance. Compensation has a significant and positive effect on employee performance. Furthermore, the Adjusted R Square value is 0.462 or 46.2%. This means that employee performance can be explained by leadership style and compensation of 46.2%, the remaining 54.8% is explained by other factors not examined in this study. The implications of this research are expected to be a benchmark for the company PT. Anwar Construction to improve employee performance.